Characterizing the most demanding passages of kinematic and mechanical activity in elite football: a multifactorial approach - Yousefian, Farzad; Zafar, Abdullah; Fransson, Dan; Mohr, Magni; Brito, João; Travassos, Bruno (Biology of Sport, 2024)
This study investigated the 5-minute most demanding passages (MDP) of kinematic (distance covered) and mechanical (acceleration and deceleration) activities in elite male football according to multifactorial criterion performance variables. Global positioning systems data were collected from 39 players across 45 matches in the Swedish first division ( n = 329 observations). The multifactorial kinematic variable (MDPk) was composed of the concurrent distances covered at moderate-speed running, high-speed running, and sprinting distances, and the multifactorial mechanical (MDPm) considered the concurrent occurrences of high intensity acceleration and deceleration activities. A moving average method was used to identify the MDP across a 5-minute period. The frequency distribution of the multifactorial variables, and differences in the time of occurrence and magnitude between multifactorial performance variables and their univariate constituent variables were investigated. Frequency distribution analysis revealed MDPk and MDPm peaked in the first 5 min of the match (MDPk: χ 2 (15, N = 329) = 135.88, p ≤ 0.001, W : 0.64, 115.99±32.7 s; MDPm: χ 2 (15, N = 329) = 31.02, p ≤ 0.001, W : 0.31, 101.21±25.1 s; p ≤ 0.0004). Within each half, differences in the MDP commencement time between the multifactorial variables and their respective discrete univariate constituent variables were trivial to small (MDPk effect size (ES): 0.04–0.21; MDPm ES: 0.02–0.11). Linear mixed model analysis demonstrated that the MDP magnitude of multifactorial variables were approximately 8–28% and 8–21% lower across the match and halves, respectively, compared to the MDP of their respective univariate constituent variables ( p ≤ 0.001; r = 0.26–0.62). The greatest differences between the respective multifactorial and discrete constituent variables were observed for sprinting (-28%) and high intensity acceleration (-22%). The results reveal that the MDP is distinguished based on peak kinematic and mechanical demands, which occur at discrete periods and exhibit distinct locomotor profiles across the match and within each half. Practitioners should consider the methods of identifying the MDP, as the selection of univariate and multifactorial kinematic and mechanical performance variables can impact MDP characterization, which can qualify the designing of bespoke training protocols.